AD 69 emperors, armies & anarchy - Fields, Nic (Pen & Sword Military, 2014)
With the death of Nero by his own hand on 9 June, AD 68, the Iulio-Claudian dynasty came to an end, and Rome was up for the taking. Nero's death threw up a critical question for the Empire. The result was that generals of the empire fell into a bloody power struggle to decide who had the right to wear the imperial purple.